Identification of key chromium resistance genes in Cellulomonas using transcriptomics - Hongmei Sun; Yongdong Li; Shengchao Gao; Guangchuan Shi; Lianbin Cao; Xinya Li; Tong Li; Tongbiao Li; Mingcheng Wang; Enzhong Li; Junhe Liu; Hongxia Ni; et al. (Ecotoxicology and Environmental Safety)
Cellulomonas fimi Clb-11 can reduce high toxic Cr(VI) to less toxic Cr(III), and transcriptomics was used to reveal the key Cr(VI) uptake and reduction genes of C. fimi Clb-11 in this study. The results showed that under 0.5 mM Cr(VI) stress, 654 genes were upregulated. Among the upregulated genes, phosphate transport protein encoding genes phoU and TC.PIT, and molybdate transport protein encoding genes modA, modB, and modC were involved in the cell uptake of Cr(VI). Cytochrome c subunits encoding genes qcrA and qcrC were involved in the intracellular reduction of Cr(VI), and cytochrome c oxidase subunits encoding genes coxB and coxC were involved in extracellular electron secretion. Additionally, several unreported genes were found to be upregulated in C. fimi Clb-11 under Cr(VI) stress. The upregulated manganese transport protein encoding gene mntH may also assist Cr(VI) uptake in C. fimi Clb-11. Proton pump subunit encoding genes atpA, atpB, atpE, atpF, and atpH, as well as sodium-hydrogen antiporter subunit encoding genes mnhA and mnhC were upregulated, it may be involved in the extracellular proton secretion to reduce Cr(VI). Iron complex transport system substrate-binding protein encoding gene ABC.FEV.S, vacuolar iron transporter encoding gene VIT, FMN reductase gene encoding gene ssuE, and quinone oxidoreductase encoding genes qor and qorB were upregulated to reduce Cr(VI) in the intracellular. Our study showed theoretical importance by revealing the Cr(VI) reduction mechanism using chrome-resistant microorganisms.